Behaviour of strengthened timber beams using carbon fiber reinforced polymer - Ahmad, Yusof (Faculty of Civil Engineering, 2008)
Nowadays, construction industry keen on finding the material to replace concrete and steel. Timber, a renewable construction material has been given more attention in the research. Moreover, with the existing of Fiber Reinforced Polymer (FRP) as a strengthening material, timber is potentially to become a popular construction material. Timber or existing timber structures can be strengthened using FRP bonding system, a system that been reported to be more effective than steel bonding system among others due to its lightweight for easy handling during construction. This research project was conducted in order to investigate the behavior of timber beams strengthened with Glass Fiber Reinforced Polymer (GFRP) rods and Carbon Fiber Reinforced Polymer (CFRP) plates. One of the beams was tested as unstrengthened control beam while five of the beams with same dimension are strengthened and tested to failure under four point loading. The size of each beam was 100Ã—200Ã—3000 mm. The behavior of the beams was studied through their load-deflection characteristics upon loading, timber and FRP strain and mode of failure. The results showed that the strengthened beams performed better than the control beam with nominal increase in stiffness and higher ultimate load. Timber beam strengthened with FRP has an increase in its ultimate load carrying capacity. The percentage of increase is 6 % to 15 % for beam strengthened with GFRP rods, and 24 % to 32 % for beam strengthened with CFRP plates. The strengthening of timber beam with FRP has enhanced the stiffness of the beam.